HASIL BELAJAR SEJARAH DENGAN MODEL EXAMPLES NON EXAMPLES DAN PICTURE AND PICTURE - Selamat Efendi; R. Gunawan Sudarmanto; Iskandar Syah (Faculty of Teacher Training and Education, University of Lampung, 2013)
This study was conducted to determine: differences in the history of student learning outcomes through the learning model examples and non-examples picture and picture, the difference between the initial capability of high, medium, and low on the history of student learning outcomes, differences in learning outcomes antarmodel students learning history and inter initial capabilities, the interaction between the model of learning with students' prior knowledge, and a more effective learning model between the model of learning examples and non-examples picture and picture. The results showed: there are differences in the history of student learning outcomes through the learning model examples and non-examples picture and picture, there is a difference between the initial capabilities of high, medium, and low on the history of student learning outcomes, no difference in outcome learn the history of student learning and inter antar model initial capabilities, there is no interaction between the model of learning with students' prior knowledge, and learning model examples non examples is more effective than learning model picture and picture.Penelitian ini dilakukan untuk mengetahui: perbedaan hasil belajar sejarah siswa melalui model pembelajaran examples non examples dan picture and picture, perbedaan antara kemampuan awal tinggi, sedang, dan rendah terhadap hasil belajar sejarah siswa, perbedaan hasil belajar sejarah siswa antarmodel pembelajaran dan antartingkat kemampuan awal, interaksi antara model pembelajaran dengan kemampuan awal siswa, dan model pembelajaran yang lebih efektif antara model pembelajaran examples non examples dan picture and picture. Hasil penelitian menunjukan: ada perbedaan hasil belajar sejarah siswa melalui model pembelajaran examples non examples dan picture and picture; ada perbedaan antara kemampuan awal tinggi, sedang, dan rendah terhadap hasil belajar sejarah siswa; ada perbedaan hasil belajar sejarah siswa antarmodel pembelajaran dan antartingkat kemampuan awal, tidak ada interaksi antara model pembelajaran dengan kemampuan awal siswa, dan model pembelajaran examples non examples lebih efektif dibandingkan dengan model pembelajaran picture and picture.Kata kunci: model pembelajaran, kemampuan awal, hasil belajar